Oral Manifestations in COVID-19 Patients Associated with Oral Hygiene in Aceh, Indonesia: A Literature Review - Hanum, Misra; Abdat, Munifah; Nurjannah, Nurjannah; Saputra, Irwan; Usman, Said (Kesmas, 2023)
COVID-19 became a pandemic because of its high-speed transmission via salivary and airborne droplet routes. Viruses can enter host cells through ACE-2 receptors in various human organs, including the oral cavity. The oral manifestations that arise include white plaque, ulceration, burning sensation, oral mucositis, depapillation of the tongue, dry mouth, halitosis, and loss of the sense of taste. Poor oral hygiene, comorbidities, decreased immunity, and stress can exacerbate these manifestations. This review study aimed to report various oral manifestations of COVID-19 related to oral hygiene. Relevant articles were identified from PubMed, ScienceDirect, Elsevier, and Google Scholar. Out of the 60 articles selected, only 36 could be reviewed. The World Health Organization recommends early detection for individuals with suspected exposure to the COVID-19 virus to control its spread, including checking for oral manifestations. Oral hygiene is an important factor affecting the manifestations of the oral cavity of COVID-19 patients, so examination of the condition of oral hygiene is recommended in the medical management of COVID-19 patients. To conclude, oral hygiene is related to the emergence of oral manifestation in COVID-19-infected patients.